MicroRNA-181a-5p alleviates acute liver failure in mice by inhibiting HMGB1: MicroRNA-181a-5p targets HMGB1 to ameliorate ALF - Zhang, Qianwen; He, Yiyu; Xu, Hao; Zeng, Yuqiao; Wang, Li; Xue, Zengxi; Sun, Qingyun; Wang, Likun (Cellular and Molecular Biology, 2023)
MicroRNAs (miRNAs) control liver diseases, but the role of microRNA-181a-5p in acute liver failure (ALF) is unclear. In this study, the ALF model was generated by injection of D-galactosamine (D-GalN) and lipopolysaccharide (LPS). The levels of miRNAs were assessed by microarray and qRT-PCR. The expression of caspase 3 was detected as the marker of cell apoptosis in ALF by immunohistochemistry and western blot. The targeting of microRNA-181a-5p on the high mobility group box 1 (HMGB1) was verified by dual luciferase assay. The impact of microRNA-181a-5p and HMGB1 was explored by flow cytometry. Results showed that microRNA-181a-5p was significantly down-regulated by D-GalN/LPS in vivo and in vitro, while the level of HMGB1 was up-regulated after the challenge. Furthermore, microRNA-181a-5p overexpression attenuated cell apoptosis in D-GalN/TNF-treated BNLCL2 cells. MicroRNA-181a-5p could directly target HMGB1 mRNA and repress its expressions, in further HMGB1 is involved in microRNA-181a-5p effect on cell apoptosis of ALF. In conclusion, these findings demonstrate that microRNA-181a-5p regulates hepatocyte apoptosis via HMGB1 in the development of ALF, which may provide potential therapeutic targets for ALF. However, the precise underlying mechanism that connects microRNA-181a-5p and HMGB1 remains to be explored.